THE ROLE OF EXTENSIONAL STRUCTURES ON EXPERIMENTAL CALDERAS AND RESURGENCE - Acocella V.; Funiciello R.; Marotta E.; Orsi G.; de Vita S. (My University, 2004)
The structure and shape of collapses and resurgences is often controlled by pre-existing discontinuities, such as normal faults in rift zones. In order to study the role of extensional structures on collapse and resurgence, we used analogue models. Dry sand simulated the brittle crust; silicone, located at the base of the sand-pack, simulated magma. In the experiments, regional extension pre-dated collapse or resurgence, forming normal faults in a graben-like structure; the graben was filled with additional sand, simulating post-rift deposits. A piston then moved the silicone downward or upward, inducing collapse or resurgence within the previously deformed sand. The collapses showed an ellipticity (length of minor axis/length of major axis) between 0.8 and 0.9, with the major axis parallel to the extension direction. The partial reactivation of the pre-existing normal faults was observed during the development of the caldera reverse faults, which, conversely to what was expected (from experiments without pre-existing extension), became partly inward dipping. Resurgence showed an elongation of the uplifted part, with the main axis perpendicular to the extension direction. At depth, pre-existing normal faults were partly reactivated by the reverse faults formed during resurgence; these locally became outward dipping normal faults. A total reactivation of pre-existing faults was also observed during resurgence. The experiments suggest that the observed elongation of calderas and resurgences is the result of the reactivation of pre-existing structures during differential uplift. Such a reactivation is mainly related to the loss in the coefficient of friction of the sand. The results suggest that elliptic calderas and resurgences in nature may develop even from circular magma chambers.
Keywords: EXTENSIONAL STRUCTURES; CALDERA; RESURGENCE; ANALOGUE MODELS; REACTIVATION